Gómez-Díaz, Raquel y Agustín-Lacruz, Carmen (2025). Con Netflix y a lo loco: aprender y entretenerse. Editorial UOC. Profesional de la información; 60. - Ríos Hilario, Ana B. (Cuadernos de Documentación Multimedia, 2025)
Review of the book titled "With Netflix and Crazy: Learning and Entertainment" by authors Raquel Gómez-Díaz and Carmen Agustín-Lacruz, published by UOC Publishing.